2009
DOI: 10.1111/j.1600-0668.2008.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Real-time or faster-than-real-time simulation of airflow in buildings

Abstract: Real time flow simulation is crucial for emergency management in buildings, such as fire and accidental or intentional release of chemical/biological agents (contaminants). The simulation results can then be used to impose proper measures to minimize casualties. The computational fluid dynamics (CFD) is accurate, but too time consuming. Nodal models are fast, but not informative. To obtain a fast and informative solution, this study proposes an intermediate approach between nodal models and CFD by introducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(77 citation statements)
references
References 23 publications
0
73
0
Order By: Relevance
“…The Reynolds-Averaged Navier-Stokes (RANS) equations are adopted together with the two-equation renormalized group RNG k-ε turbulence model, due to its capability of accurate prediction of turbulent indoor airflows at low-Reynolds number with and without flow swirl, as previous studies have shown good model performances in terms of accuracy, numerical stability and short computing time [36,39]. In the energy equation, radiation heat generation from a heating source is also included through a Discrete Ordinates (DO) model already implemented in ANSYS Fluent software and it is applied with various angular discretisation and sub-iteration parameters to control solid angles in discretising each octant of the angular space and volume overhang on each surface respectively, so that radiative conditions can be applied to each individual faces and fluid elements within the computational domain.…”
Section: Airflow and Heat Transfermentioning
confidence: 99%
“…The Reynolds-Averaged Navier-Stokes (RANS) equations are adopted together with the two-equation renormalized group RNG k-ε turbulence model, due to its capability of accurate prediction of turbulent indoor airflows at low-Reynolds number with and without flow swirl, as previous studies have shown good model performances in terms of accuracy, numerical stability and short computing time [36,39]. In the energy equation, radiation heat generation from a heating source is also included through a Discrete Ordinates (DO) model already implemented in ANSYS Fluent software and it is applied with various angular discretisation and sub-iteration parameters to control solid angles in discretising each octant of the angular space and volume overhang on each surface respectively, so that radiative conditions can be applied to each individual faces and fluid elements within the computational domain.…”
Section: Airflow and Heat Transfermentioning
confidence: 99%
“…On the other hand, the numerical viscosity is not turbulent viscosity so that the FFD model has difficulties to precisely predict the turbulent flows. In addition, simply adding turbulence models into the FFD cannot improve the prediction for turbulence (Zuo and Chen, 2009) since the flow will become too viscous with both numerical and turbulent viscosities. To improve the accuracy of the FFD model, it is necessary to reduce the numerical viscosity.…”
Section: Analysis Of Numericical Diffusion In Ffd Modelmentioning
confidence: 99%
“…However, most indoor airflow is turbulent (Lariani et al, 2009). Our previous work (Zuo and Chen, 2009) tried to predict turbulent flow by adding turbulence models in the FFD. Unfortunately, it did not provide satisfactory results due to the large numerical viscosity in the linear interpolation.…”
Section: Disucssionsmentioning
confidence: 99%
See 2 more Smart Citations